2018
DOI: 10.1021/acs.jmedchem.8b00375
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent 2-Aryl-6,7-dihydro-5H-pyrrolo[1,2-a]imidazoles as WDR5-WIN-Site Inhibitors Using Fragment-Based Methods and Structure-Based Design

Abstract: WDR5 is a chromatin-regulatory scaffold protein overexpressed in various cancers and a potential epigenetic drug target for the treatment of mixed-lineage leukemia. Here, we describe the discovery of potent and selective WDR5-WIN-site inhibitors using fragment-based methods and structure-based design. NMR-based screening of a large fragment library identified several chemically distinct hit series that bind to the WIN site within WDR5. Members of a 6,7-dihydro-5 H-pyrrolo[1,2- a]imidazole fragment class were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 37 publications
(83 reference statements)
1
63
0
Order By: Relevance
“…While the zero atom linker showed little binding ( 13 , K D = 5.2 mM), a linker length of one, two, or three methylene units was tolerated ( 14 , K D = 530 μ M, 15 , K D = 300 μ M, and 16 , K D = 140 μ M, respectively). Interestingly, the weakly binding fragment 13 is similar to the imidazole fragment hit reported by Wang et al 28 The subtle difference in orientation between the two series' imidazole rings appears key to avoid clashes with nearby residues S49 and I305. A cocrystal structure bound with 16 was solved, showing the introduced phenyl ring projecting into subpocket S4, toward residues A47, S49, A65, and L321 [Fig.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…While the zero atom linker showed little binding ( 13 , K D = 5.2 mM), a linker length of one, two, or three methylene units was tolerated ( 14 , K D = 530 μ M, 15 , K D = 300 μ M, and 16 , K D = 140 μ M, respectively). Interestingly, the weakly binding fragment 13 is similar to the imidazole fragment hit reported by Wang et al 28 The subtle difference in orientation between the two series' imidazole rings appears key to avoid clashes with nearby residues S49 and I305. A cocrystal structure bound with 16 was solved, showing the introduced phenyl ring projecting into subpocket S4, toward residues A47, S49, A65, and L321 [Fig.…”
Section: Resultssupporting
confidence: 59%
“…This compound inhibits the histone methyltransferase (HMT) activity of MLL1 in vitro and reduces the viability of primary human AML cells bearing C/EBPα mutations 24 and inhibits “gain-of-function” p53 cell growth 26 . Recently, an NMR-based fragment screen identified several high-affinity WIN-site binders 28,29 . These compounds show cellular activity through displacement of WDR5 from chromatin, an effect that gives WDR5 inhibitors therapeutic relevance beyond MLL-r cancers 29 .…”
Section: Introductionmentioning
confidence: 99%
“…To identify small molecules that bind the WIN site, we conducted a fragment-based screen of ~13,800 compounds by acquiring SOFAST 1 H- 15 N heteronuclear multiple quantum coherence (HMQC) spectra of WDR5 ( Wang et al, 2018 ). An initial HMQC spectrum of uniformly 15 N-labeled WDR5 with an unlabeled MLL1 WIN peptide highlighted peak shifts that correspond to amino acids in the vicinity of the WIN site.…”
Section: Resultsmentioning
confidence: 99%
“…One of these fragment hits is compound C1 ( Figure 1A ), which binds WDR5 with a K d of ~66 μM ( Table S1 ). We solved the X-ray crystal structure of C1 when complexed with WDR5 ( Figure 1B ; Table S2 ) and found that the cyclic guanidine of C1 binds deep into the S 2 pocket of WDR5 ( Wang et al, 2018 ), mimicking the arginine of the WIN peptide. To improve the affinity of C1, we used structure-based design to access nearby pockets.…”
Section: Resultsmentioning
confidence: 99%
“…This result has clinical significance because there are now several small molecule inhibitors of WDR5 used in both in vitro and in vivo studies, including OICR-9429 [25]. There are also more specific emerging inhibitors of WDR5 with a higher IC 50 that have been recently developed [26]. The available targeted drugs for patients with advanced-stage papillary thyroid carcinoma remain limited.…”
Section: Discussionmentioning
confidence: 99%